TECHNOFERENCE IN PARENTING: IMPLICATIONS FOR PARENT–CHILD EMOTIONAL INTERACTION IN THE DIGITAL ERA - Ratu Balqis, Rizqiyah; Putri Maja Mulia Kulzum (Department of Pendidikan Guru Madrasah Ibtidaiyah Universitas Islam Negeri Alauddin Makass, 2025)
The phenomenon of technoference, the disruption of social interactions due to parental use of gadgets, is increasingly evident in family life in the digital era. This condition impacts the quality of communication and emotional closeness between parents and children, especially elementary school-aged children (7–12 years old) who are at a sensitive stage of social-emotional development. This study aims to explore parents' experiences of technoference in parenting patterns and its implications for emotional interactions with children. A qualitative approach with a phenomenological design was used, involving 13 parents selected through purposive sampling. Data were obtained through in-depth interviews and validated with member checking, then analyzed using the Colaizzi method. The results of the study revealed three main themes: (1) weakening emotional bonds when parents' attention is distracted by gadgets, (2) emotional ambivalence in the form of guilt and justification for gadget use, and (3) protective strategies based on local wisdom and religious values ​​such as eating together, congregational prayer, tadarus (recitation of the Koran), and traditional games. These findings confirm that technoference has a negative impact on family emotional interactions but can be minimized through strengthening character education. The implication is that the results of this study can be the basis for developing family-based digital literacy programs to strengthen the emotional bond between children and parents in the digital era.